Family Christmas at Frances Kamp's San Mateo Home - Watkins, Howard::::::::: (1984)
Jerry Kamp in back, Markita Smith, Adam Watkins, Howard Watkins holding Robin Watkins, Juanita Smith, Frances Kamp, Christine Watkins, Jackie Hijmans with Cary Hijmans in front yard